Pengaruh Interaksi Host dan Jumlah Penonton Saat Live Streaming Selling TikTok Terhadap Purchase Intention Konsumen - Vandela Yence, Yora; Sriwahyuni, Eka; Afrianto, Eeng Juli (Masyarakat Ekonomi Syariah Bogor, 2025)
The objectives of this study are to examine the influence of host interaction during TikTok live streaming selling on consumer purchase intention, to analyze the impact of the number of viewers on consumer purchase intention, to identify and analyze factors affecting consumer purchase intention during TikTok Live sales, and to explore the implementation of Islamic marketing principles in live streaming sales activities on TikTok. This research employs an explanatory research design with a quantitative approach. The data analysis techniques include research instrument testing, classical assumption testing, and multiple linear regression analysis or hypothesis testing using IBM SPSS 26. The findings indicate that host interaction has a partial influence on consumer purchase intention, while the number of viewers in live streaming selling also has a partial influence on consumer purchase intention. Furthermore, the results reveal that host interaction and the number of viewers simultaneously influence consumer purchase intention by 69.8%, while the remaining 31.2% is affected by other variables outside the scope of this study.